492 Calcific Tendonitis of the Longus Colli: A Rare Cause of Neck Pain. (19th August 2022) - Bryce, A; Douglas, C; Williamson, A
Abstract: Cervical tendonitis of the Longus Colli muscle (CTLC) is a rare but clinically significant cause of neck pain. It can mimic other more serious pathologies in the retro-pharygneal area and requires sufficient investigation for diagnosis. This case presented with a fit and well 54-year-old gentleman suffering from progressive left sided neck pain, stiffness, and odynophagia. His imaging demonstrated a prevertebral fluid collection of unclear aetiology and an area of calcification just below the anterior arch of C1. Along with the differential diagnosis of calcific tendonitis of longus colli, the fluid collecting inferior to C1 could have represented a retropharyngeal abscess - a potentially life-threatening infection. This patient required input from multiple specialities to safely reach diagnosis and exclude more significant pathology. Although CTLC represents a benign and perhaps under-recognised condition, this case highlights the importance of considering other differential diagnoses and multidisciplinary management in a patient presenting with limited neck movements.